O setor industrial brasileiro frente à integração econômica - Silva, Mygre Lopes da (2018)
The industrial sector is one of the main drivers of economic growth, due to the spillover effects passed on to other sectors of the economy. In Brazil, the industrial sector has been losing competitiveness due to the growth of industrial costs and the penetration of Chinese industrial products in the market. In this sense, the consolidation of trade agreements may lead to changes in the economies, especially in developing countries, which show a share of income from international trade. In this way, the objective of this work is to analyze the impact in the Brazilian industrial sector of the consolidation of the regional trade agreements, such as Trans-Pacific Partnership (TPP), Transatlantic Trade and Investment Partnership (TTIP) and Mercoeuro. More specifically, we seek to analyze trade flows, quantity produced, domestic prices, welfare levels and GDP. To this end, the Global Trade Analysis Project (GTAP-9). In this sense, two scenarios were estimated, the first with elimination of import tariffs among the members of the agreements, and the second, including elimination of production subsidies and export. In both scenarios there are losses of consumer welfare and GDP, revealing that these deals are detrimental to the economy as a whole. The results of the first scenario indicate that the economic impacts on the Brazilian industry of low and medium-low; medium-high and high technological intensity, are relatively small. In the second scenario, the gains of the industrial sector are relatively higher, once the subsidies are eliminated. The consolidation of all the trade agreements analyzed are detrimental to the country in terms of consumer welfare and GDP. The industrial sectors of low and medium-low and medium-high and high technological intensity benefit from gains in competitiveness. Export and import subsidies have led to significant changes in world trade, particularly in the automotive and air vehicle sectors.